EFEKTIVITAS PENANGANAN KLAIM KENDARAAN DI PT. JASARAHARJA PUTERA CABANG PALEMBANG - AUSTIN, TRECY; Trecy Austin; Aulia Kurniati, Maygita; Berlian, Ong; Hakim, Arif Rahman; Sobri (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
Handling vehicle claim at PT. Jasaraharja Putera Palembang Branch refers to the process of submitting and settling vehicle insurance claim being carried out efficiently, on time, and meeting the expectations of policy holders and this research aims to identify obstacles faced in the process of handling claim and provide recommendations for improvement. The research uses qualitative methods with Ricard M. Steers' theory which has 3 dimensions, namely goal achievement, integration and adaptation. The results of this research indicate that the effectiveness of handling vehicle claim at PT. Jasaraharja Putera Palembang Branch has not been effective, with obstacles in the dimension of achieving goals seen from the aspect of the achievement period and concrete targets that have been running well. Integrity dimensions, seen from the aspects of procedures and socialization processes, there is still a lack of understanding from insurance companies towards customers, causing customers to lack understanding of the claim submission process. The adaptation dimension consists of aspects of increasing capabilities and infrastructure which have not been running well because customers feel limited in their choice of workshops and often have to travel long distances to get repair estimates. Based on these three dimensions, it can be seen that the effectiveness of handling vehicle claim at PT. Jasaraharja Putera Palembang Branch has not been effective due to a lack of socialization on claim handling procedures and a lack of facilities and infrastructure at the recommended workshops